Christmas Tree: Ritual, Globalization, and Ocean Preservation in Tanimbar Island - Frejhon Cleimen Lasatira (Eastasouth Institute, 2026)
This article examines the entanglement of ritual practice, globalization, and indigenous ecological ethics through the unique case of Christmas tree performances in Tanimbar Island, Eastern Indonesia. While the Christmas tree originates as a European Christian cultural invention, its arrival in Tanimbar—mediated by Dutch missionaries—generates a radically different mode of ritualization and ecological engagement. Drawing on autoethnographic fieldwork, this study identifies three key dynamics: (1) the Christianization and emotionalization of the Christmas tree as a liturgical symbol; (2) the community’s deliberate rejection of industrial and plastic Christmas trees associated with global markets; and (3) the use of mangrove trees (Tongke) as Christmas trees framed within local cosmology, SASI customary law, and oceanic ecological ethics. The findings demonstrate that Tanimbar communities situate Christmas not merely as a religious ritual but as a negotiation of identity, ecological stewardship, and resistance to global debates on religion, ecology, and indigenous knowledge by demonstrating how Christian rituals are reindigenized, ocean-centered, and ecologically restorative.